Intelligent control method and system for vibroflotation construction in hydropower engineering - Qixiang Fan; Guo Li; Xiaochun Jiang; Bin Ma; Tao Chen; Meng Li (Journal of Intelligent Construction)
The vibroflotation construction is a significant measure for foundation improvement in hydropower engineering. Currently, vibro-stone columns are still constructed manually. The construction process relies mainly on the experience and responsibility of workers, which has the shortcomings of low precision in pile formation control and low degree of automation, leading to problems such as uneven pile formation, high labor intensity, and poor pile quality. This study proposes an intelligent vibroflotation control model (iVCM) based on the analysis of the pile formation mechanism and former experiences. Intelligent control of vibroflotation construction is realized through intelligent control of the vibrator current, rope pull, filler amount, and vibrator depth. A crane-type intelligent vibroflotation control system was developed to realize one-button intelligent control of pile formation. Its application in Yingliangbao Hydropower Station shows that the intelligent vibroflotation control system can regulate the construction operation of the pile formation process, improve the vibroflotation quality, reduce labor intensity, and have prospects for applicability in similar projects.